Alectinib Salvages CNS Relapses in ALK-Positive Lung Cancer Patients Previously Treated with Crizotinib and Ceritinib. Issue 2 (February 2015) - Gainor, Justin F.; Sherman, Carol A.; Willoughby, Kathryn; Logan, Jennifer; Kennedy, Elizabeth; Brastianos, Priscilla K.; Chi, Andrew S.; Shaw, Alice T.
<x xml:space="preserve">Abstract</x> Background: Leptomeningeal metastases (LM) are an increasingly frequent and devastating complication of anaplastic lymphoma kinase (ALK)-rearranged non–small-cell lung cancer (NSCLC). Currently, the optimal management of LM in ALK-positive patients remains poorly understood as these patients have been routinely excluded from clinical trials. Methods: We describe four ALK-positive patients with LM who were treated with the next-generation ALK inhibitor alectinib through single-patient, compassionate use protocols at two institutions. All patients had previously been treated with both FDA-approved ALK inhibitors—crizotinib and ceritinib. Patients received alectinib at a starting dose of 600 mg twice daily. Results: Four ALK-positive NSCLC patients with symptomatic leptomeningeal disease were identified. Three of four patients experienced significant clinical and radiographic improvements in LM upon treatment with alectinib. A fourth patient had stable intracranial disease for 4 months before eventual systemic disease progression. Overall, alectinib was well tolerated. One patient required dose reduction due to grade 2 hyperbilirubinemia. Conclusions: Alectinib is active in ALK-rearranged NSCLC patients with LM, including in patients previously treated with crizotinib and ceritinib. Additional prospective studies of alectinib in ALK-positive patients with LM are warranted.